(3QSGdI aj Yde GdcjejGAs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3gPg QSGdI CYedgG GdTjN CHh Ydi SjfG ai GdMceI GdeSJhQI bGd LQi Hjfi hHjf GdTjN ajeG JYQag eYGQVI hGdJeS efi JbQjQ Pdc ai LRA djchf Pdc JPcQI GdaUd GdChd ai GdGeQ Gdcdi s
(3BNQgG (B:s
(3eKGd GdRFHb GdeGA heKGd GdcdS GdGQV hGdGUaQ HGdGQHYI cdgG hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
Keywords: (3GdcjejGA h GdWHjYjGJs